2019
DOI: 10.1007/s11912-019-0768-4
|View full text |Cite
|
Sign up to set email alerts
|

How Recent Advances in Biology of Waldenström’s Macroglobulinemia May Affect Therapy Strategy

Abstract: Purpose of Review Waldenström macroglobulinemia (WM) is a rare lymphoproliferative disorder. Up to now, therapeutic choice was not influenced by the biological characteristics of the disease. Here, we will review how recent advances in biology in WM may affect therapy strategy. Recent Findings Recently, WM has been described as a new oncogenic model. MyD88 mutation has been described as a key driver mutation and has functional consequences which could be targeted. Other mutations, such as CXCR4 or TP53, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…9 The frequency of CXCR4 MUT patients in our trial was higher than previously described (56%), likely as a result of the sensitivity of the deep NGS strategy and digital PCR, as well as the relapse setting. 34,35 We did not find any difference in time to response, quality of response, or PFS according to CXCR4 mutation profile or type of mutation (frameshift [FS] vs nonsense [NS]), in contrast to previously described patients treated with ibrutinib. 35 TP53 mutations were observed in 24% of the patients in our R/R cohort, which is also higher than previously described at diagnosis.…”
Section: Inclusion N=50contrasting
confidence: 66%
“…9 The frequency of CXCR4 MUT patients in our trial was higher than previously described (56%), likely as a result of the sensitivity of the deep NGS strategy and digital PCR, as well as the relapse setting. 34,35 We did not find any difference in time to response, quality of response, or PFS according to CXCR4 mutation profile or type of mutation (frameshift [FS] vs nonsense [NS]), in contrast to previously described patients treated with ibrutinib. 35 TP53 mutations were observed in 24% of the patients in our R/R cohort, which is also higher than previously described at diagnosis.…”
Section: Inclusion N=50contrasting
confidence: 66%
“…Considered as secondary genetic events, activating mutations of CXCR4 (CXCR4 S338X or CXCR4 WHIM ), a receptor implicated in migration and bone marrow (BM) homing of leucocytes, are found in 30% of WM cases ( 6 ). Additional mutations of CD79b , ARID1A or TP53 have been reported ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances, WM pathophysiology is incompletely understood. Its treatment remains challenging and the exact role of MYD88 mutations in the emergence of lymphoplasmacytic B-cell clones is not known ( 7 , 8 ). Indeed, MYD88 mutations are also found in 30% of activated B-cell type diffuse large B-cell lymphomas (ABC-DLBCL), more than half of primary cutaneous DLBCLs, leg type, and many DLBCLs at immune-privileged sites but not in plasma cell myelomas, even IgM types ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The significant degree of clinical and genetic heterogeneity can be attributed mostly to WM tumoral clone compartment which consists of clonal B-cells, clonal plasma cells and a lymphoplasmacytic population [7,20]. Whole-genome sequencing studies have shown recurrent somatic mutations in WM and IgM MGUS as the most important prognostic markers defining prognosis, risk of progression, and treatment decisions [21]. Previous GEP profiling studies have identified several pathways and gene expression alterations in WM and IgM MGUS patients [15,16].…”
Section: Discussionmentioning
confidence: 99%